Antecedents of successful commercial biogas implementation in South Africa - De Bondt, Albert Stefanus (My University, 2018)
Despite its demonstrated ability to provide benefits to the user and the environment, the commercial dissemination of biogas in South Africa has been less favourably received than other renewable energy technologies which have advanced drastically over the last decade. By means of literature review and interviews with key stakeholders in the biogas industry, this study sought to identify and understand the factors necessary for commercial biogas implementation in South Africa to succeed. The study focuses on the South African context, in contrast to other economic or technological-only analyses that have been done previously. Enhancements to energy security and environmental security were found to be the most prominent enablers for biogas; mainly that biogas dissemination can help alleviate municipal, agricultural and industrial organic effluent load into the South African ecosystems. It is further emphasised that the continued sustainability and proper management of the environment is an important factor for economic progress and sustainability, and that biogas implementation can assist in achieving this. Biogas has not been explicitly incorporated into commercial-scale energy and waste policies, nor has it received the necessary attention within the environmental incentives of the Republic of South Africa. The concurrent lack of enforcement of the existing waste management regulations results in alternatives for industries to dispose of organic waste in a cheaper and sometimes less responsible manner. This study proposes that the value proposition of biogas in South Africa should be positioned primarily as a significant and effective organic waste abatement function instead of a tool for energy production, and that biogas should receive separate attention from a policy and incentives perspective.
MBA
Keywords: Biomass energy -- Economic aspects. Biogas. Biomass energy -- Social aspects.